2014
DOI: 10.1177/1358863x14528271
|View full text |Cite
|
Sign up to set email alerts
|

Statin use is associated with improved overall survival without affecting patency and limb salvage rates following open or endovascular revascularization

Abstract: The aim of the study was to determine statin drug association with patency, limb salvage rates and survival after revascularization in patients with chronic limb ischemia. We retrospectively reviewed all patients who underwent revascularization for intermittent claudication or critical limb ischemia between 05/2001 and 12/2009. Patients were grouped based on statin therapy at the time of revascularization. Early postoperative outcomes as well as patency, limb salvage, and survival rates were compared between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
2
14
1
Order By: Relevance
“…Our observation corroborates reports by other authors who found that optimal medical treatment had a significant influence on the outcome of endovascular therapy [2,3,10,11], and statins helped to salvage limbs after percutaneous intervention [17][18][19][20][21][22][23][24][25]. Only Dosluoglu et al [26] were unable to confirm a favourable statins effect on limb salvage. In the context of the above-mentioned data, the significant negative effect of blood LDL cholesterol level on the risk of amputation seems to be strange (Tab.…”
Section: Discussionsupporting
confidence: 89%
“…Our observation corroborates reports by other authors who found that optimal medical treatment had a significant influence on the outcome of endovascular therapy [2,3,10,11], and statins helped to salvage limbs after percutaneous intervention [17][18][19][20][21][22][23][24][25]. Only Dosluoglu et al [26] were unable to confirm a favourable statins effect on limb salvage. In the context of the above-mentioned data, the significant negative effect of blood LDL cholesterol level on the risk of amputation seems to be strange (Tab.…”
Section: Discussionsupporting
confidence: 89%
“…32 Analyses from large registries have observed an association between lower amputation rates and statin therapy; however, the potential for residual confounding has remained and the intensity of statin therapy or achieved LDL-C was not reported. 6,33,34 Smaller observational studies in patients with critical limb ischemia have shown mixed results for the association between statins in limb events with some showing no significant reduction in amputation and others showing improved limb salvage in patients presenting for endovascular therapy for critical limb ischemia. 29,30,35 The current study demonstrates that nonstatin LDL-C lowering added to statins reduces MALE in patients with symptomatic atherosclerosis and that the benefits extend to very low achieved LDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…32 Another observational analysis evaluated 717 patients undergoing revascularization for intermittent claudication or CLI, of whom 55.4% were on statins. 129 After adjustment, statin therapy was associated with increased survival; however, there was no associated benefit of statin therapy on long-term vessel patency or limb salvage. 129 Although individual trials show varied results, the overall data suggest a beneficial effect of lipid-lowering therapy, and in particular statin therapy, for limb outcomes, including worsening claudication, walking time, and limb vascular events of CLI, ALI, and amputation.…”
Section: Statin Therapymentioning
confidence: 99%
“…129 After adjustment, statin therapy was associated with increased survival; however, there was no associated benefit of statin therapy on long-term vessel patency or limb salvage. 129 Although individual trials show varied results, the overall data suggest a beneficial effect of lipid-lowering therapy, and in particular statin therapy, for limb outcomes, including worsening claudication, walking time, and limb vascular events of CLI, ALI, and amputation. Although high-intensity statin therapy is already indicated in symptomatic PAD patients, these findings may play a role in understanding the broad importance of widespread use and compliance in patients with PAD.…”
Section: Statin Therapymentioning
confidence: 99%